Anti‐tumor effects of an antagonistic mAb against the ASCT2 amino acid transporter on KRAS‐mutated human colorectal cancer cells. (10th November 2019) - Hara, Yuta; Minami, Yushi; Yoshimoto, Soshi; Hayashi, Natsumi; Yamasaki, Akitaka; Ueda, Shiho; Masuko, Kazue; Masuko, Takashi
Abstract: KRAS mutations are detected in numerous human cancers, but there are few effective drugs for KRAS ‐mutated cancers. Transporters for amino acids and glucose are highly expressed on cancer cells, possibly to maintain rapid cell growth and metabolism. Alanine‐serine‐cysteine transporter 2 (ASCT2) is a primary transporter for glutamine in cancer cells. In this study, we developed a novel monoclonal antibody (mAb) recognizing the extracellular domain of human ASCT2, and investigated whether ASCT2 can be a therapeutic target for KRAS ‐mutated cancers. Rats were immunized with RH7777 rat hepatoma cells expressing human ASCT2 fused to green fluorescent protein (GFP). Splenocytes from the immunized rats were fused with P3X63Ag8.653 mouse myeloma cells, and selected and cloned hybridoma cells secreting Ab3‐8 mAb were established. This mAb reacted with RH7777 transfectants expressing ASCT2‐GFP proteins in a GFP intensity‐dependent manner. Ab3‐8 reacted with various human cancer cells, but not with non‐cancer breast epithelial cells or ASCT2 ‐knocked out HEK293 and SW1116 cells. In SW1116 and HCT116 human colon cancer cells with KRAS mutations, treatment with Ab3‐8 reduced intracellular glutamine transport, phosphorylation of AKT and ERK, and inhibited in vivo tumor growth of these cells in athymic mice. Inhibition of in vivo tumor growth by Ab3‐8 was not observed in HT29 colon and HeLa uterus cancer cells with wild‐type KRAS . These results suggest that ASCT2 is an excellent therapeutic target for KRAS ‐mutated cancers. Abstract : ASCT2 is a major glutamine transporter in various cancer cells, and higher expression of ASCT2 is correlated with poor prognosis of cancer patients. This study strongly suggests that ASCT2 is an excellent target molecule for the treatment of malignancies, especially KRAS ‐mutated cancers.